Posterior Ganglion Cyst of the Knee Treated by Ultrasound-Guided Aspiration with Adjunctive Saline Injection: A Case Report - John Christian Parsaoran Butarbutar; Joshua Edward Hananto; Henoch Gugun Parulian Siahaan; Yee Wen Yong (Universitas Airlangga, 2026)
Background: Ganglion cysts around the knee, particularly those originating from the gastrocnemius muscle, are uncommon and may cause significant posterior knee discomfort. Although surgical excision remains the gold standard, it carries risks such as postoperative complications, recurrence, and prolonged recovery.Case Report: A 41-year-old male presented with a 10-year history of posterior knee pain, aggravated during squatting and the Jalsa position during Islamic prayer. Physical examination revealed tenderness in the popliteal fossa without ligamentous instability. Ultrasound (US)-guided aspiration was performed, yielding approximately 4 mL of yellow, viscous fluid, followed by the injection of 10 mL of normal saline to facilitate cyst wall rupture and collapse, without corticosteroid use. This minimally invasive modification may reduce recurrence while avoiding potential steroid-related adverse effects. Immediate improvement in knee mobility was observed. At the 4-month follow-up, complete symptom resolution was reported, and all daily activities, including Islamic prayer, were performed without restriction. Follow-up US imaging confirmed a reduction in cyst size.Discussion: Ganglion cysts can be effectively managed with minimally invasive approaches such as ultrasound-guided aspiration, which offers precise localization and reduced complication risk compared to surgery. In this case, adjunctive saline injection facilitated cyst collapse and resulted in excellent functional recovery, although recurrence remains a possibility.Conclusion: US-guided aspiration with adjunctive saline injection is a promising alternative to surgical excision; however, further studies are needed to confirm its long-term efficacy.